Enteric methane mitigation through Asparagopsis taxiformis supplementation and potential algal alternatives - Wasson, Derek E.; Yarish, Charles; Hristov, Alexander N. (Frontiers in Animal Science, 2022)
Macroalgae supplementation has emerged as a promising tool to mitigate enteric methane emission in ruminants. The mode of action responsible for the mitigation effect centers around the content of volatile halogenated compounds, primarily bromoform. The sub-tropical red seaweed, Asparagopsis taxiformis, is the most well researched bromoform containing species. While several studies, both in vitro and in vivo, have demonstrated the effectiveness of A. taxiformis at reducing enteric methane emission (> 80% reduction), questions surrounding sustainability, animal productivity, human health, and commercial practicality remain. These questions by no means disqualify the practice of feeding macroalgae to cattle to reduce methane emission, but they must be answered before implementing macroalgae as a feed additive commercially. Also, limiting scientific inquiry to a few species reduces the potential of discovering other compounds and modes of action that could produce the desired mitigation effect without the inherit drawbacks of the current options. Work conducted in both ruminant nutrition and human health fields have identified numerous bioactive compounds within macroalgae that exhibit anti-microbial functions that could modify the rumen microbiome for beneficial outcomes. Phlorotannins, saponins, sulfonated glycans, other halocarbons and bacteriocins found within macroalgae have demonstrated antimicrobial activity in vitro. However, it is unclear what effect these compounds may have when used in vivo. Variation in active ingredient concentration, palatability to cattle, and excessive dietary mineral content are all limitations on how much macroalgae can be included in ruminant diets. There are multiple in vitro studies that have demonstrated a methane reduction potential of non-bromoform containing species, but inclusion levels are often well above the effective levels of A. taxiformis (< 0.5% of dietary dry matter). In some animal studies, A. taxiformis supplementation has led to decreased dry matter intake and productivity and elevated mineral accumulation, such as iodine, in animal products. Therefore, methane mitigation by macroalgae will likely have to occur at low dietary concentrations to be practical. This review aims to highlight potential benefits and challenges that feeding macroalgae as a tool for methane reduction may have on animal production, the environment, animal and human health.